EFFECT OF AMIODARONE IN PREVENTION OF ATRIAL FIBRILLATION IMMEDIATELY AFTER RELEASE OF AORTIC CROSS-CLAMP - Sahu, Lingaraj; Samantaray, Alok; Behera, Shashi Sankar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to determine the efficacy of a bolus dose of amiodarone administered by the way of cardiopulmonary bypass pump before releasing of aortic cross-clamp (ACC) in the prevention of atrial fibrillation. Methods: In this prospective study, 22 non-diabetic patients were randomly assigned in a double-blind fashion to either amiodarone or placebo group. In amiodarone group injection amiodarone 3 mg/kg in 10 ml normal saline (amiodarone group, Group A, n=10) and in control group (control group, Group P, n=12), the same volume of normal saline was administered 3 min before the release of ACC. Initial rhythm after the release of ACC was noted. Results: The major rhythm after the release of ACC was ventricular arrhythmia in control group (n=5, 40%), whereas in amiodarone group, it is normal sinus rhythm (n=7, 63%). Only the need of cardioversion/defibrillation and the amount of energy needed was less in the amiodarone group but not reached statistical significance level. There was a trend toward a higher ventricular rate in control group compared to amiodarone group, but it never reached statistical significance level (114±46 vs. 97±29, p=0.3). One patient in amiodarone group required temporary pacemaker for sustained atrioventricular block with heart rate of <50 beats/min and continued on temporary pacemaker for 48 h.